Recovery of Learning Lack Post Pandemi Covid 19 (Study of Policy Implementation Based on Ministry of Education and Culture No. 56 of 2022 Concerning Guidelines for Implementing the Independent Curriculum at SMKN I AL-Mubarkeya Aceh Besar) - Rahmi Isra; Bambang Satriya; Kridawati Sadhana (Britain International for Academic Research (BIAR) Publisher, 2023)
In order to restore learning lag (learning loss)After the Covid 19 Pandemicat Al-Mubarkeya Aceh Besar Vocational High School (SMK), implementing an independent curriculum according to the conditions of the education unit and students,based on the Ministry of Education and Culture policy Number 56 of 2022 concerning guidelines for implementing learning. Based on the reality in the implementation of the independent curriculum, it is necessary to have an in-depth study of teacher creativity as the spearhead in implementing the independent curriculum. The purpose of the research is to describe and analyze the implementation of the Ministry of Education and Culture's policy No. 56 of 2022 concerning Guidelines for the Implementation of the Independent Curriculum at SMKN I AL-Mubarkeya Aceh Besar in the recovery of learning after the Covid 19 Pandemic as well as describe and analyze the creativity of SMK Negeri 1 Al-Mubarkeya teachers in recovery Post-Covid 19 Pandemic learning based on the Independent Curriculum. The research method used in this study is a qualitative method. Through qualitative methods the researcher wants to gain in-depth understanding and thoughts regarding social reality and relevant facts related to the implementation of the independent curriculum. Data collection was carried out through observation and interviews, while the sources were determined by purposive sampling of 9 people. The results of the research show that in the implementation of the Ministry of Education and Culture policy No. 56 of 2022 concerning the implementation of the independent curriculum,teacher's ability to master technology is still limited, facilities are also still limited, but there is a change for the better in terms ofthe level of understanding of students because learning is more enjoyable due to the freedom to choose subjects and essential material towards soft skills. Then there is also a limited number of modules as teaching materials available in the implementation of the independent curriculum covered by the creativity of the teacher, making it easier to achieve learning.